IMPLEMENTASI KEBIJAKAN FESTIVAL TELUK JAILOLO (FTJ) STUDI DIKABUPATEN HALMAHERA BARAT - MAIS, TRISNO; AREROS, WILLIAM; EGETEN, MAXI (JURNAL ADMINISTRASI PUBLIK, 2019)
The regional government of West Halmahera Regency through the Tourism Office in 2009 sees it importantto develop the tourism sector. Through local policy, the government took a strategic step by scheduling theJailolo Bay Festival (FTJ) to be held every year. Explicitly, the objective of the Jailolo Bay Festival (FTJ)is to promote tourism.This research method uses qualitative research methods. In this study is to analyze the factors associatedwith the implementation of the Jailolo Bay Festival (FTJ) policy in West Halmahera Regency.The author considers that the implementation of the Jailolo Bay Festival (FTJ) has been effective. Thiscertainly can be seen from a number of factors, the most obvious is that, from the implementation of theactivity, it can encourage a number of tourists to visit West Halmahera RegencyThe organizer of the Jailolo Bay Festival (FTJ) has had a positive impact on the local government andcommunity. Because after this activity is carried out, visiting tourists visiting tourist areas continue to arrive.Keywords: Policy Implementation, Jailolo Bay Festival